Pregabalin and Gabapentin's Effectiveness Safety in Treating Neuropathic Pain are Compared at Pakistan Institute of Medical Sciences in Islamabad - Muhammad Usman, Sawaira Gul, Syed Wajahat Ali Shah, Hafiza Maryam Munir, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with neuropathic pain treated at a single clinic in Pakistan took part in this research study over six months to assess the efficacy and safety of pregabalin and gabapentin as potential treatments. Patients suffering from neuropathic pain and participating in the experiment were split into two groups, each receiving pregabalin or gabapentin according to a random assignment. Before being evaluated using the Visual Analogue Pain Scale (VAS), participants were first questioned about their demographics and the degree of their pain at the beginning of the study. Follow-up appointments were held one week, one month, three months, and six months after the first visit. According to the research results, both pregabalin and gabapentin helped reduce neuropathic pain; however, the effects of pregabalin on pain reduction were much more significant. It was determined that both drugs were safe to use, and none of the reported adverse effects were particularly severe. Both gabapentin and pregabalin were found to be effective drugs in relieving neuropathic pain by the researchers who conducted the study. Objectives: The primary objective of this study is to ascertain whether or not pregabalin and gabapentin are helpful in the treatment of neuropathic pain in patients who are receiving care at the Pakistan Institute of medical sciences Islamabad, Pakistan. The secondary objective of this research is to evaluate the effectiveness of pregabalin and gabapentin in reducing the amount of pain that participants in the study report feeling. The Visual Analogue Scale, often known as the VAS, will quantify the pain level experienced. Methods: A study effort meeting the requirements for a single center, the double-masked, placebo-controlled open trial, was conducted Department of Medicine Pakistan Institute of medical sciences (pims) from jan through july 2022 in Pakistan. Based on a random selection, patients were administered either pregabalin or gabapentin. During follow-up appointments scheduled one week, one month, three months, and six months following their first evaluation, they were evaluated using the Visual Analogue Pain Scale (VAS), which comprised a baseline assessment of demographic information and the baseline degree of their pain. In case there were any unintended adverse effects from the study medication, all of the subjects were maintained under close monitoring. The primary success indicator for this inquiry is the shift in the VAS score. Results: Pregabalin and gabapentin both reduced neuropathic pain, according to one research. The pregabalin group saw a VAS score change that was substantially larger than that of the gabapentin group compared to the baseline (p 0.001). Compared to the baseline, the mean VAS score decrease in the pregabalin group at six months was statistically significant (p 0.001). For either medicine, there were no severe adverse effects documented. Conclusion: According to the study's findings, gabapentin and pregabalin are both reliable medications for treating neuropathic pain. Pregabalin was shown to have a higher decrease in VAS score at six months than gabapentin did in terms of lowering pain intensity. Keywords: Pregabalin, Gabapentin, Neuropathic Pain, Efficacy, Safety, Visual Analogue Pain Scale (VAS).